Biomechanical and clinical differences in muscle tone, stiffness, range of motion, and pain perception in children with cerebral palsy: a cross-sectional study - González-Matilla, Ramón; Abuín-Porras, Vanesa; Mínguez-Esteban, Isabel; Heredia-Rizo, Alberto M. (Frontiers in Physiology, 2025)
IntroductionSpasticity and altered muscle tone are key features in children with neurodevelopmental disorders, particularly cerebral palsy (CP). They impact movement, range of motion (ROM), and pain perception, influencing functional abilities and quality of life. Understanding the intrinsic muscle differences in children with CP can help improve clinical assessment and therapeutic interventions. This study aims to evaluate differences in muscle tone, stiffness, ROM, and pain perception between children with CP and typically developing peers using objective biomechanical measures.MethodsAn observational, cross-sectional study was conducted with 40 participants of both sexes (20 children with CP, 20 typically developing peers). Muscle tone and stiffness of the lower limb muscles were measured using the Myoton PRO device. ROM was assessed by goniometry, and pain perception was evaluated using the Visual Analog Scale during a Straight Leg Raise (SLR) test. A generalized linear mixed model was used to detect differences in myotonometry, ROM, and pain perception measurements. In participants with CP, the Pearson product-moment correlation coefficient analysis was used to explore possible associations between clinical features and muscle tone and stiffness.ResultsChildren with CP exhibited reduced ROM, with a significant group effect for hip flexion (P < 0.001; η2 = 0.843), knee extension (P < 0.001; η2 = 0.355), and ankle flexion (P < 0.001; η2 = 0.959) and higher pain perception during the SLR test (P < 0.001; η2 = 0.831), compared to controls. Myotonometry revealed significantly increased muscle stiffness of the rectus femoris (P = 0.004; η2 = 0.112) and adductor muscles (P = 0.019; η2 = 0.074) in the CP group, with no differences in muscle tone between the groups. Sex-related differences were found for muscle tone and stiffness, with males showing higher values. Correlation analyses indicated that adductor muscles stiffness was associated with CP severity.ConclusionChildren with CP demonstrate significant changes in ROM, pain perception, and muscle stiffness, emphasizing the need for targeted therapeutic interventions. These findings support the use of objective biomechanical tools for assessing muscle properties in clinical settings, contributing to better management strategies for spasticity-related impairments.